Massive radiation in Ammopelmatus Jerusalem crickets (Orthoptera: Stenopelmatoidea: Stenopelmatinae): Phylogenomics, revision, and biology of 105 new species from the United States and Mexico - Weissman, David B.; Weissman, Daniel W.; Vandergast, Amy G.; Ueshima, Norihiro; Warchałowska-Śliwa, Elżbieta; Song, Hojun (Zootaxa, 2026)
We review and discuss all named United States and Mexico species of Ammopelmatus Tinkham Jerusalem crickets, even if synonymized in earlier literature. We recognize as valid 12 previously named taxa: A. cahuilaensis (Tinkham), A. comanchus (Saussure & Pictet), A. davewerneri (Tinkham), A. fuscus (Haldeman), A. intermedius (David & Smith), A. kelsoensis Tinkham, A. longispinus (Brunner von Wattenwyl), A. mescaleroensis (Tinkham), A. muwu Rentz & Weissman, A. navajo (Rentz), A. nigrocapitatus (Tinkham & Rentz), and A. pictus (Scudder). We confirm A. californicus (Brunner von Wattenwyl) as a junior synonym of A. longispinus. We synonymize A. monahansensis (Stidham & Stidham) under A. mescaleroensis. We designate neotypes for A. fuscus and A. mescaleroensis. We declare the following 6 names to be nomen dubium: A. cephalotes (Walker), A. fasciatus (Thomas), A. hydrocephalus (Brunner von Wattenwyl), A. irregularis (Brunner von Wattenwyl), A. oculatus (Scudder), and A. terrenus (Rehn). We recognize 11 major clades, and 26 Groups within those 11 clades, delimited by DNA, morphology, karyotype, ecology, and calling drum pattern. In their phylogenetic tree order, we recognize (1) the Winchester Group, with 11 (possibly 12) species; (2) the Big Sur Group, with 1 species; (3) the Longispinus Group, with 12 species; (4) the Portal Group, with 2 species; (5) the Argus Group, with 5 species; (6) the Mojave Desert Group, with 8 species, 1 which is tentative; (7) the Springville Group, with 1 species; (8) the Lightfooti Group, with 10 species; (9) the Smithi Group, with 3 species; (10) the Grayi Group, with 1 species; (11) the Southern California Group #1, with 4 species; (12) the Southern California Group #2, with 4 species; (13) the Southern California/Baja California Group #3, with 9 species; (14) the Lincoln County Group, with 1 species; (15) the Utah Group, with 3 species; (16) the Fuscus Group, with 5 species, 2 of which are tentative; (17) the Mono Lake Group, with 7 species; (18) the Muwu Group, with 1 species; (19) the Pratti Group, with 1 species; (20) the Fast Drumming Group, with 13 species; (21) the Vandenberg Air Force Base Group, with 2 species; (22) the San Gabriel/ Pelona Mts Group, with 2 species; (23) the Islander Group, with 2 species; (24) the Southern California Group #4, with 3 species; (25) the Southern California Group #5, with 2 species; and (26) the Monica Mts Group, with 2 species; We describe the following 105 taxa as new: A. abelai Weissman, A. acton Weissman, A. angelusoaks Weissman, A. anzaborrego Weissman, A. argus Weissman, A. ashleighi Weissman, A. bajasur Weissman, A. bakersfield Weissman, A. ballmeri Weissman, A. ballonadark Weissman, A. bartonflats Weissman, A. bigsur Weissman, A. brachysocius Weissman, A. briani Weissman, A. brockovichi Weissman, A. bruneaudunes Weissman, A. calimesa Weissman, A. carsoncity Weissman, A. castaneus Weissman, A. catalinae Weissman, A. cathedralgorge Weissman, A. cedarview Weissman, A. chimineas Weissman, A. chinalake Weissman, A. christmasvalleydunes Weissman, A. clarki Weissman, A. coralpink Weissman, A. coyflat Weissman, A. crypticus Weissman, A. danieli Weissman, A. descansodunes Weissman, A. dogtown Weissman, A. eatoncanyon Weissman, A. ensenada Weissman, A. etiwanda Weissman, A. evansi Weissman, A. finnon Weissman, A. fisheri Weissman, A. fremontpeak Weissman, A. glacierlodge Weissman, A. glennville Weissman, A. gomezfarias Weissman, A. grahami Weissman, A. grapevine Weissman, A. grayi Weissman, A. hovorei Weissman, A. icenoglei Weissman, A. idaho Weissman, A. intermedioides Weissman, A. islander Weissman, A. joshuatree Weissman, A. juniperdunes Weissman, A. kennedymeadows Weissman, A. kennedymeadowsdos Weissman, A. kirai Weissman, A. knighti Weissman, A. kokoweef Weissman, A. lagunahanson Weissman, A. lakecachuma Weissman, A. lakesherwood Weissman, A. larumorosa Weissman, A. leei Weissman, A. lightfooti Weissman, A. lincolncounty Weissman, A. longispinoides Weissman, A. mahogani Weissman, A. monolake Weissman, A. mtpinos Weissman, A. mtshasta Weissman, A. oneillpark Weissman, A. owensvalley Weissman, A. pinnacles Weissman, A. pinyonpines Weissman, A. piute Weissman, A. portal Weissman, A. pratti Weissman, A. reno Weissman, A. rentzi Weissman, A. rusti Weissman, A. sakai Weissman, A. sandiego Weissman, A. sanfrancisco Weissman, A. sangabriel Weissman, A. sanjacinto Weissman, A. sanmartinensis Weissman, A. sanpedromartir Weissman, A. santarosaplateau Weissman, A. sierrapelona Weissman, A. skinner Weissman, A. smithi Weissman, A. sonoraensis Weissman, A. springville Weissman, A. stringfellow Weissman, A. tarcanyon Weissman, A. tehachapi Weissman, A. temblor Weissman, A. tomsplace Weissman, A. vandenberg Weissman, A. warnermts Weissman, A. westgardpass Weissman, A. whitewater Weissman, A. winnemucca Weissman, A. wrightwoodi Weissman, A. yubalake Weissman, and A. zayante Weissman. Ammopelmatus has its highest species’ diversity in Southern and Central California, with most taxa having limited distributions; and with most species nearest genetic relative usually being geographically close. Six newly described taxa rank as the six heaviest insect species in California, with some adults exceeding 12 grams. Where two Ammopelmatus species are sympatric, we present data that indirectly suggest that calling song drums may act as a premating barrier; and that diploid chromosome number may act as a post mating barrier.